2008
DOI: 10.2478/v10032-008-0014-3
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics of Fresh Plant Sprouts and After Their Short-term Storage

Abstract: SummarySensory characteristics, carotenoids content and antioxidant activity of sprouted seeds of eight plant species were investigated. Seeds of lentil, broccoli, clover, amaranth, wheat, radish, pea, and alfalfa were germinated for 3 days in the dark, at the temperature of 25ºC and then sprouted seeds were stored for the next 2 days in a refrigerator, in the dark, at the temperature of 4-5ºC. Sensory quality was evaluated in the expert panel, with the quantitative descriptive analysis method (QDA), using 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…As various sprouts contain many phytochemicals, so the pro-health impacts of sprouts have already been the focus of different studies [16,29,30,37]. Plants eaten raw are the main sources of dietary antioxidants such as polyphenols, vitamins C and E, carotenoids, phytates, thiocyanates, indols and various minerals with antioxidant properties, which play a significant role in the reduction of human metabolic diseases, hence the public in high-and some middle-income countries are interested in the antioxidant properties of such foods and their influence on human health [37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As various sprouts contain many phytochemicals, so the pro-health impacts of sprouts have already been the focus of different studies [16,29,30,37]. Plants eaten raw are the main sources of dietary antioxidants such as polyphenols, vitamins C and E, carotenoids, phytates, thiocyanates, indols and various minerals with antioxidant properties, which play a significant role in the reduction of human metabolic diseases, hence the public in high-and some middle-income countries are interested in the antioxidant properties of such foods and their influence on human health [37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…That is why we determined the effect of Zn on the DNA markers profile of sprouts, as high accumulation of heavy metals can cause DNA damage [10,11]. We used random amplification of polymorphic DNA (RAPD) markers, a useful and powerful technique for various polymorphism analyses including genetic diversity and similarity, cultivar identification and phylogenetic analysis of many plant species [12][13][14][15][16]. RAPD markers are also useful for studying variability in in vitro cultures [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Ga jewski con firms the high qual ity of sprouts of len tils, clo ver, broccoli, peas, wheat, rad ishes and al falfa col lected on the 3rd day of growth and stored for 2 days. Or gano lep tic test ing has shown that the domi nant sen sory char ac ter is tics of len til sprouts are their pea-like odour, grainy tex ture, and sweet taste [7].…”
Section: Resultsmentioning
confidence: 99%
“…For example, sprouts from Fabaceae family seeds, such as lentils, peas, beans, and some legumes, taste bitter because of their high polyphenol content [10]. In contrast, high amounts of glucosinolates give a spicy taste to Cruciferous family sprouts such as radish and broccoli sprouts [11,12]. Color is another important external quality parameter that affects overall acceptability.…”
Section: Important Quality Attributes Of Sproutsmentioning
confidence: 99%